STRATEGI PEMASARAN AGROINDUSTRI KUE BOLU DI KECAMATAN KUOK KABUPATEN KAMPAR - Evy Maharani; Dian Wulandari (Indonesian Journal of Agricultural Economics, 2014)
Small business activities are agro-processing activities supported by the government both plantation and agro-industry agro-industry food as relatively well-established industrial and developing better than other sectors, and employment both for employers and the surrounding environment. This study aims to formulate a marketing strategy agroindustrial sponge cake in District Kuok Kampar regency. This research was conducted in the village of Kuok, Kuok District of Kampar regency in August 2014. The method used in this research is survey methods, sampling was done intentionally (purposive sampling) based on the largest cake production and the long business experience. The sample in this study consisted of an agro-industry entrepreneurs sponge cake and sponge cake 30 consumers. This study uses primary data and secondary data. The analysis is A'WOT, A'WOT is a combination of AHP and SWOT analysis. Determining factors of each component of SWOT and weighting obtained from interviews with respondents expert, and became expert in this study is the first person of entrepreneurs sponge cake, 1 of Industry and Trade, one person from the District, one person out of the workforce, and 1 person from consumers. The results showed that the marketing strategy a top priority can be applied in agroindustrial sponge cake is 1) Expanding marketing with a priority value of (0.165), 2) Maintaining the quality and quantity of products with a priority value of (0.161), 3) Improving the marketing of products with a priority value by (0.149), 4) creating packaging innovation by providing the brand with a priority value of (0.131), 5) Maintain product prices remain affordable to view market information with a priority value of (0.093), 6) Minimizing costs with a priority value of ( 0.086), 7) Following the exhibition and establish cooperation with food stores such as supermarkets to increase the sale with a priority value of (0,085), 8) Maintain product with a priority value of (0,074), and 9) promotion by following the events important to priority value of (0.056).